An Analysis of Communication Strategies Upon Video Blog of English Education Students - Dian Rahma Santoso; Vidya Mandarani (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
The utilization of both social media within a communication context progressed as the flow of technological development goes on. One of the most popular examples is the use of video blog within our daily life. This interlanguage study which is presented using a descriptive qualitative method is specifically made with the aim to investigate communication strategies employed by 44 fourth-semester students of English Education Study Program as their effort in accomplishing a field trip project of describing public places into a video blog. The field trip was on July 27th to 29th, 2018 in Yogyakarta, Central Java. Students were expected to compose and submit a video blog of themselves describing a particular public place fully in English during their trip. Thus, the instruments involved are video documentation, which was in the form of students’ video blog, and an open-ended interview. The findings show that communication strategies used by students’ video blogs include 6 direct, 2 indirect and 1 interactional strategies to overcome communication difficulties, which in turn will assist them in composing longer videos and making them widely understandable for most non-native English speakers.